Drug-induced fall risk in older patients: A pharmacovigilance study of FDA adverse event reporting system database - Zhou, Shuang; Jia, Boying; Kong, Jiahe; Zhang, Xiaolin; Lei, Lili; Tao, Zhenhui; Ma, Lingyue; Xiang, Qian; Zhou, Ying; Cui, Yimin (Frontiers in Pharmacology, 2022)
Objectives: As fall events and injuries have become a growing public health problem in older patients and the causes of falls are complex, there is an emerging need to identify the risk of drug-induced falls. Methods: To mine and analyze the risk signals of drug-induced falls in older patients to provide evidence for drug safety. The FDA Adverse Event Reporting System (FARES) was used to collect drug-induced fall events among older patients. Disproportionality analyses of odds ratio (ROR) and proportional reported ratio (PRR) were performed to detect the adverse effects signal. Results: A total of 208,849 reports (34,840 fall events and 1,898 drugs) were considered. The average age of the included patients was 76.95±7.60 years, and there were more females (64.47%) than males. A total of 258 drugs with positive signals were detected to be associated with drug-induced fall risk in older patients. The neurological drugs (104, 44.1%) with the largest number of positive detected signals mainly included antipsychotics, antidepressants, antiparkinsonian drugs, central nervous system drugs, anticonvulsants and hypnotic sedatives. Other systems mainly included the circulatory system (25, 10.6%), digestive system (15, 6.4%), and motor system (12, 5.1%). Conclusion: Many drugs were associated with a high risk of falls in older patients. The drug is one of the critical and preventable factors for fall control, and the risk level of drug-induced falls should be considered to optimize drug therapy in clinical practice.